2020
DOI: 10.1111/jam.14880
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of insecticide flonicamid by Aminobacter sp. CGMCC 1.17253 via nitrile hydratase catalysed hydration pathway

Abstract: Aims This study evaluates flonicamid biotransformation ability of Aminobacter sp. CGMCC 1.17253 and the enzyme catalytic mechanism involved. Methods and Results Flonicamid transformed by resting cells of Aminobacter sp. CGMCC 1.17253 was carried out. Aminobacter sp. CGMCC 1.17253 converts flonicamid into N‐(4‐trifluoromethylnicotinoyl) glycinamide (TFNG‐AM). Aminobacter sp. CGMCC 1.17253 transforms 31·1% of the flonicamid in a 200 mg l−1 conversion solution in 96 h. Aminobacter sp. CGMCC 1.17253 was inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…According to our earlier research, the N 2 -fixing bacteria Variovorax boronicumulans CGMCC 4969, Microvirga flocculans CGMCC 1.16731, Aminobacter sp. CGMCC 1.17253, Ensifer meliloti CGMCC 7333, and E. adhaerens CGMCC 6315 efficiently convert FLO to TFNG-AM using NHases [ 16 , 17 , 18 , 19 , 20 ]. V. boronicumulans CGMCC 4969 and M. flocculans CGMCC 1.16731 hydrolyze TFNG-AM to TFNG using amidases but do not hydrolyze TFNA-AM, another intermediate of FLO.…”
Section: Introductionmentioning
confidence: 99%
“…According to our earlier research, the N 2 -fixing bacteria Variovorax boronicumulans CGMCC 4969, Microvirga flocculans CGMCC 1.16731, Aminobacter sp. CGMCC 1.17253, Ensifer meliloti CGMCC 7333, and E. adhaerens CGMCC 6315 efficiently convert FLO to TFNG-AM using NHases [ 16 , 17 , 18 , 19 , 20 ]. V. boronicumulans CGMCC 4969 and M. flocculans CGMCC 1.16731 hydrolyze TFNG-AM to TFNG using amidases but do not hydrolyze TFNA-AM, another intermediate of FLO.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Aminobacter sp. CGMCC 1.17253 (Yang et al, 2021a), Ensifer meliloti CGMCC 7333 (Yang et al, 2021b), Ensifer adhaerens CGMCC 6315 (Zhao et al, 2021b), and Microvirga flocculans CGMCC 1.16731(Zhao et al, 2020; Zhao et al, 2021a) have been reported to degrade FLO via NHase/amidase pathway. Nevertheless, FLO degradation by nitrilase (EC 3.5.5.1) has been poorly understood.…”
Section: Introductionmentioning
confidence: 99%